Driving, Pseudo‐reality and the BTK: A Case Study. Issue 3 (10th June 2015) - Lynes, Adam; Wilson, David
Abstract The significance of occupational choice, in particular those that involve driving, has not yet been studied or investigated in relation to serial murder. This paper, which adopts a case study approach, attempts to shed light on how driving as an occupation may instrumentally influence the offending behaviour of one North American serial murderer—Dennis Rader. Attention is given towards how spending such significant amounts of time driving may have held deep psychological importance for Rader, with regard to the development of his offending‐oriented fantasies. In particular, the "offending space model" is used to examine the relationship between 'thinking and doing'. In providing this micro‐level analysis, we suggest that transient oriented occupations provide a rich array of practical advantages that may aid serial murderers in avoiding detection, whilst also holding deep psychological influence in the nurturing and development of their fantasies. Copyright © 2015 John Wiley & Sons, Ltd.